2013
DOI: 10.1186/1748-717x-8-142
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of proton beam therapy for advanced neuroblastoma

Abstract: PurposeTo evaluate the efficacy of proton beam therapy (PBT) for pediatric patients with advanced neuroblastoma.MethodsPBT was conducted at 21 sites in 14 patients with neuroblastoma from 1984 to 2010. Most patients were difficult to treat with photon radiotherapy. Two and 6 patients were classified into stages 3 and 4, respectively, and 6 patients had recurrent disease. Seven of the 8 patients who received PBT as the initial treatment were classified as the high risk group. Twelve patients had gross residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
(20 reference statements)
3
17
0
1
Order By: Relevance
“…We did not exclude any patients with local failures occurring within 12 months. Our study adds to the scant proton literature and is consistent with the existing proton and photon literature with longer follow‐up . The predominant site of failure is progression in post‐induction non‐MIBG‐avid distant sites, similar to previously published reports .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We did not exclude any patients with local failures occurring within 12 months. Our study adds to the scant proton literature and is consistent with the existing proton and photon literature with longer follow‐up . The predominant site of failure is progression in post‐induction non‐MIBG‐avid distant sites, similar to previously published reports .…”
Section: Discussionsupporting
confidence: 89%
“…At the University of Pennsylvania, all 11 children treated with proton therapy to the primary site were locally controlled at a median follow‐up of 16 months . In another study from Japan, 14 patients (8 high‐risk and 6 recurrent neuroblastoma) received proton therapy with a three‐year locoregional control rate of 82% . Compared with the above, our study has a longer median follow‐up of 60.2 months, with a larger number of patients, and looked at local control at both primary and irradiated metastatic sites.…”
Section: Discussionmentioning
confidence: 96%
“…In PBT, the tumor control rate is similar to that in photon radiotherapy [9][10][11][12][13][14][15][16][17][18][19][20], but late toxicity and the secondary cancer risk should be much lower due to the dose distribution [21]. For this reason, PBT has potential as a treatment for pediatric tumors, but fewer institutions have proton beam centers compared to those with normal photon radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Proton beam radiation therapy has been shown to reduce the side effects of radiation therapy by minimizing doses of radiation delivered to normal tissues surrounding treated tumors [75]. Although the use of proton beam radiation in children with neuroblastoma has been hampered by both cost and limited access, early studies have suggested that proton beam radiation may provide some benefit to children with advanced neuroblastoma [76,77], and further studies are underway to better evaluate the safety and efficacy of proton beam radiation for children with neuroblastoma (NCT02112617).…”
Section: Local Controlmentioning
confidence: 99%